(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The importance of consonants in connected speech is examined in this article. Consonants have a major impact on spoken language's rhythm, intelligibility, and fluency through their interactions with vowels and other phonetic components. Through an analysis of phonological processes like linking, elision, and assimilation, the paper demonstrates how consonants modify in continuous speech to preserve communication effectiveness. It provides information about how changes to consonants affect speech processing, pronunciation, and language acquisition.